Association of ATM Gene Polymorphism with PTC Metastasis in Female Patients - Yulu Gu; Xiaoli Liu; Yaqin Yu; Jieping Shi; Lizhe Ai; Hui Sun; Joseph Sam Kanu; Chong Wang; Yawen Liu (International Journal of Endocrinology)
Ataxia telangiectasia mutated (ATM) gene is critical in the process of recognizing and repairing DNA lesions and is related to invasion and metastasis of malignancy. The incidence rate of papillary thyroid cancer (PTC) has increased for several decades and is higher in females than males. In this study, we want to investigate whether ATM polymorphisms are associated with gender-specific metastasis of PTC. 358 PTC patients in Northern China, including 109 males and 249 females, were included in our study. Four ATM single nucleotide polymorphisms (SNPs) were genotyped using Matrix-Assisted Laser Desorption/Ionization Time of Flight Mass Spectrometry (MALDI-TOF-MS). Association between genotypes and the gender-specific risk of metastasis was assessed by odds ratios (OR) and 95% confidence intervals (CI) under the unconditional logistic regression analysis. Significant associations were observed between rs189037 and metastasis of PTC in females under different models of inheritance (codominant model: OR=0.15, 95% CI 0.04–0.56, P=0.01 for GA versus GG and OR=0.08, 95% CI 0.01–0.74, P=0.03 for AA versus GG, resp.; dominant model: OR=0.49, 95% CI 0.25–0.98, P=0.04; overdominant model: OR=0.47, 95% CI 0.25–0.89, P=0.02). However, no association remained significant after Bonferroni correction. Our findings suggest a possible association between ATM rs189037 polymorphisms and metastasis in female PTCs.